Analisis Pengaruh Disiplin Kerja, Kompetensi dan Kepercayaan terhadap Kepuasan Pasien - Iffah, Milchatul (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This study aims to test whether Work Discipline, Competence and Trust on Patient Satisfaction at the Tlogosari Wetan Health Center Semarang. The population in this study was calculated from the average patient visits based on polyclinics at the Tlogosari Wetan Semarang Health Center in the 2020-2021 period. The sample of this research is 100 respondents. The types of data used are primary data and secondary data. This study uses questionnaires, observations, and interviews, in collecting data. The data analysis method used is quantitative analysis, namely by testing the validity and reliability, classic assumption test, multiple regression analysis, t test and F test and test the coefficient of determination with the help of SPSS version 25. The results of this study indicate that: Work Discipline has no significant effect on patient satisfaction. This is evidenced by the significance level of 0.369 > 0.05 and tcount -0.902 0.05 and tcount 1.270 Ftable 2.70 The regression equation is Y = 10.050 (-0.073) X1 + (0.114) X2 + (0.242) X3 + e Keywords: Work Discipline, Competence, Trust and Patient Satisfaction.